Valuasi kesadaran lingkungan, corporate social responsibility terhadap kualitas laba dengan moderasi komite audit - Ronny Bagus Witjaksono; Syahril Djaddang (Jurnal Ekonomi dan Bisnis, 2018)
This study aims to investigate the effects of the valuation of environmental awareness and corporate social responsibility on earnings quality with the audit committee as the moderating variable. From 96 state-owned enterprises (SOEs) operating in construction and property industries, the research uses 49 of these SOEs as the sample based on the purposive sampling method. The findings suggest that there is no significant effect of environmental awareness on SOEs’ earnings quality and Corporate Social Responsibility (CSR) significantly affects SOEs’ earnings quality. However, audit committee does not moderate the effect of CSR on earnings quality. Further, on average SOEs do not present detailed information on environmental items regarding to the accounting and financial, environmental litigation, prevention of environmental pollution, and other aspects. They only present their environment-related social activities as the voluntary disclosure. Overall, higher CSR index implies higher earnings quality. However, audit committee does not significantly affect earnings quality, probably because SOEs appoint their audit committees only to formally comply with the Financial Services Authority (OJK- Otoritas Jasa Keuangan).